NoPegida: Die helle Seite der Zivilgesellschaft? - Marg, Stine; Walter, Franz; Kopp, Julia; Schmitz, Christopher; Trittel, Katharina (transcript, 2016)
The NoPegida protests formed in many places as a reaction to Pegida, the `Patriotic Europeans Against the Islamicization of the Occident'. If Pegida was interpreted as an expression of resentments toward religious minorities, the `lying press' and the `traitors'; then NoPegida is viewed as the shining counter-example: they stand for cosmopolitanism, freedom, equality and tolerance, and as such are perceived as the guardians and expression of an inclusive and functioning civil society and as the shapers of a `culture of welcoming'. But what is NoPegida really about? What motivates the protest? What do the concepts of freedom, equality, tolerance and cosmopolitanism mean to the protestors, and which political interpretive models and hierarchies of value inform them? After the successful volume on Pegida published in early 2015, the Göttinger Institute for Democracy Studies now provides a detailed image of the counter-protests, and investigates the extent to which NoPegida can be interpreted as a democratic counterpart to Pegida.